THE GREEN HOUSE GAS ABATEMENT STUDY FOR INDONESIA - Edi Sartono; Scorpio Sri Herdinie (Jurnal Pengembangan Energi Nuklir, 2001)
ABSTRACT The energy demand in Indonesia is projected to increase in the future. Based on the tentative results of the comprehensive assessment of different energy source for electricity, the demand will grow and reach the figure of about 8,200 Peta Joules in the year 2025. With regards to the energy supply in connection with climate change resulting from increasing Greenhouse Gases (GHG) in the atmosphere, and in line with the national energy policy which stresses on diversification, conservation, energy price and environmental awareness in energy supply development. The main objective of this study is to analyse GHG abatement by introduction various clean energy options such as renewable and nuclear energy in the Indonesian energy system by using IAEA Tool and to calculate the cost of GHG emission avoided. For the purpose of the case study, two cases were developed with some aggregations and assumptions for simplification. The first case Baseline case, which represents the current energy network (doing nothing case) and the second case defined GHG mitigation in the electric sector by replacing fossil power plants (600 MWe + 400 MWe) with various clean energy options GHG abatement technology (1000 MWe Nuclear PP). The result of the study shown that the total of CH4 reduction until the end of study period of about 1180.8 tons and 271.6 million tons for C02. The average reduction of the greenhouse gas are 4.4% per year for CH4 and 7.3% per year for C02, starting from introduction of nuclear power plant in year 2012. It is believed that, the economic competitiveness of nuclear power could significantly increase if GHG mitigation program were taken into account in the national energy planning. GHG abatement technology choice has to be made on the basis of economic aspects and its efficiency, so that the type of technology that is chosen is the most optimum as viewed from all aspects of the economy and the environment. Applying fuel diversification in the electric generation mix, nuclear and renewable energy, energy conservation as well as the demand side management can be carry out by mitigation of CH4 and C02 in the energy sector.